PENGARUH MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR DAN SIKAP KRITIS SISWA SEKOLAH DASAR - Connyta Elvadola; Ristika Ristika; Rahma Dhini; Putri Dian Mahira (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2019)
The purpose of this research was to find out the influence of discovery learning model to critical thinking skill and students’ result study on interactions between living things and environment subject matter. The design of this research was control group pretest-posttest. The qualitative data were critical thinking skill which obtained through perceptions of students and worksheet were analyzed by descriptive. The quantitative data were obtained pretest posttest were analyzed by t test with signification level of 5%. The result showed average of percentage critical thinking skill on experiment class (80,5%) was higher than control class (61,9%). Then, students’ result study were obtained from N-Gain score on experiment class (65) was higher than control class (50). Based on this research, it can be concluded that discovery learning model gave influence to critical thinking skill and students’ result study on interactions between living things and environment subject matter.